2006
DOI: 10.1890/0012-9658(2006)87[50:neaart]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Niche Evolution and Adaptive Radiation: Testing the Order of Trait Divergence

Abstract: In the course of an adaptive radiation, the evolution of niche parameters is of particular interest for understanding modes of speciation and the consequences for coexistence of related species within communities. We pose a general question: In the course of an evolutionary radiation, do traits related to within-community niche differences (a niche) evolve before or after differentiation of macrohabitat affinity or climatic tolerances (b niche)? Here we introduce a new test to address this question, based on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
294
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(303 citation statements)
references
References 63 publications
(69 reference statements)
8
294
1
Order By: Relevance
“…For example, Diamond (1986) proposed that New Guinean birds diverge first in habitat type and subsequently in prey size and food type; Richman and Price (1992) suggested that leaf warblers (genus Phylloscopus) diverged first in body size, then in behavior and foraging morphology, and finally in habitat use; and Streelman et al (2002) suggested that parrotfish diversified sequentially in habitat, diet, and sexually selected traits (reviewed by Streelman and Danley [2003] and Ackerly et al [2006]). These hypotheses share a common form: a clade first diversifies in one way, such as in habitat use.…”
Section: Stages Of Radiationmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Diamond (1986) proposed that New Guinean birds diverge first in habitat type and subsequently in prey size and food type; Richman and Price (1992) suggested that leaf warblers (genus Phylloscopus) diverged first in body size, then in behavior and foraging morphology, and finally in habitat use; and Streelman et al (2002) suggested that parrotfish diversified sequentially in habitat, diet, and sexually selected traits (reviewed by Streelman and Danley [2003] and Ackerly et al [2006]). These hypotheses share a common form: a clade first diversifies in one way, such as in habitat use.…”
Section: Stages Of Radiationmentioning
confidence: 99%
“…The problem with these hypotheses is that they usually rely on phylogenetic reconstruction of ancestral traits (an exception is Diamond 1986; see discussion in Ackerly et al 2006 andLosos 2009). Unfortunately, we are unlikely to be able to have much confidence in ancestral reconstructions for traits that evolve rapidly relative to the frequency of cladogenesis (Schluter et al 1997;Oakley and Cunningham 2000).…”
Section: Stages Of Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…For Ceanothus, results were averaged over a set of 100 equally parsimonious trees (57), and variation among trees was negligible for the results presented here. None of the trait data were obtained from the specimens used for molecular analysis, so trait data for species were matched to corresponding species names at the tips.…”
Section: Rates Of Evolution For Plant Ecological Traits: Case Studiesmentioning
confidence: 99%
“…The adaptive role of magnesium for peat mosses, together with the previously reported adaptive role of pH (Mikulášková et al 2015), represent a rather recent evolutionary mechanism, forming a beta niche in the sense of Ackerly et al (2006), which is in marked contrast to the adaptation to water level that drives the macroevolution of peat mosses ). An analogous pattern is recorded for vascular plants, although the physiological background of calcicole behaviour may be different .…”
Section: Magnesium Toxicity As An Evolutionary Trigger For Wetland Brmentioning
confidence: 93%